A Cathaysian rugose coral fauna from the upper Carboniferous of central Iran. (26th December 2018) - Wang, Xiangdong; Gorgij, Mohammad N.; Yao, Le
Abstract: Twelve rugose coral species belonging to seven genera are described and discussed based on 70 thin sections of 32 specimens collected from the Anarak section, northeast of Nain, Esfahan Province, Yazd Block, central Iran. These species include two new colonial rugose coral species, Antheria fedorowskii and Antheria robusta, and five previously named species of colonial rugose corals, Antheria lanceolata and Streptophyllidium scitulum, and solitary rugose corals, Arctophyllum jiangsiense, Caninophyllum cf. somtaiense, and Pseudotimania delicata . Five species are left in open nomenclature: Antheria sp., Arctophyllum sp., Caninophyllum sp., Nephelophyllum sp., and Yakovleviella sp. These Iranian corals are associated with the fusulinids Rauserites (several species) and Ultradaixina bosbytauensis, indicating a latest Carboniferous age (Gzhelian age). All the described genera and named species belong to the families Aulophyllidae, Bothrophyllidae, Cyathopsidae, and Kepingophyllidae, among which the family Kepingophyllidae has been previously documented only from China and Indochina. They are typical representatives of the Cathaysian rugose fauna, which was widely developed around the South China and Indochina blocks near the paleoequator and was absent from the Gondwanan and Cimmerian continents in high latitudes during the Late Pennsylvanian. Hence, the occurrence of the Cathaysian fauna from central Iran in the latest Carboniferous suggests that it may have had a close biogeographical connection with China and Indochina, which further implies its latitudinal position intermediate between the Gondwanan continent and South China and Indochina blocks during this time. UUID: http://zoobank.org/5257d2bb-1346-4dee-8f3e-f4b1b33ba5a9